Pathway analysis to characterize the relationships between healthcare access and healthcare visits in the United States using the health information national trends survey - Hu, Qinglin; Li, Xiaobing; Morales-Alemán, Mercedes M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Americans had fewer healthcare visits compared to their counterparts in other developed countries. The lack of regular check-ups can contribute to worsening health conditions. Insurance coverage, access to transportation to healthcare services, and having accessed health information via the internet are known to be associated with frequency of healthcare visits. However, there is limited literature detailing the direct and indirect influences of these variables on frequency of patients’ healthcare visits. We aimed to understand the interactive relationship between insurance coverage, access to transportation to healthcare services, and having accessed health information via the internet on frequency of patient healthcare visits. Methods: We used data from the 2018 Health Information National Trends Survey (N=3504), the only survey year providing the source for information on insurance coverage, access to transportation to healthcare services, and having accessed health information via the internet. We used descriptive statistics, random parameter binary logistic regression, and pathway analysis to describe and analyze the associations between these determinants of healthcare access and healthcare visits. Results: Results indicated that access to transportation to healthcare services (18.32%) and having insurance coverage (27.89%) were directly associated with healthcare visit frequency whereas the association between having accessed health information via the internet and reporting a healthcare visit, compare to the former two, was weaken (10.87%). Residential area (rural/urban), health conditions, age, race/ethnicity, employment status were directly associated with visit frequency whereas income status and education level were associated with healthcare visits indirectly through insurance. Conclusions: Better understanding interactive relationships between healthcare access determinants will be key to the development of healthcare access interventions aimed at reducing healthcare disparities.